Numerical simulation of the electric field induced in a contactless dielectrophoretic quadrupole cell separator. Issue 2 (8th August 2020) - Tada, Shigeru
Abstract : Purpose: This study aims to propose a contactless and continuous dielectrophoretic cell-separation device using quadrupole electric field. To examine the separation performance, numerical simulations of the electric field in the cross-section of the glass capillary installed in the center of the quadrupole electrode were conducted. Design/methodology/approach: To estimate the magnitude of the dielectrophoretic force induced on cells, electrostatic analysis was performed by using a boundary-fitted coordinate system.Distribution of the electric field and gradient of the electric field square in the cross-section of the glass capillary were simulated for various ratios of radii of the glass capillary to the electrode rod. Findings: The distribution of the electric field was found to have a cone-like profile about the center axis of the glass capillary with maximum at the internal surface of the glass capillary. The magnitude of the gradient of electric field square had similar distribution as that of the electric field, but had steeper slope near the internal surface of the glass capillary. The optimal values of the ratio of radii and the applied voltage were also estimated to achieve the local electric field strength suitable for cell separation. Originality/value: One major advantage of the proposed device is simple and low fabrication cost, in addition to its contactless structure free from cell damage. Derived knowledge is instructive in achieving high-throughput cell separation without the use of devices of complex structure.